Shear Wave Elastography in Placental Dysfunction: Comparison of Elasticity Values in Normal and Preeclamptic Pregnancies in the Second Trimester. (1st January 2015) - Cimsit, Canan; Yoldemir, Tevfik; Akpinar, Ihsan Nuri
Abstract : Objectives: The aim of this study was to determine whether shear wave elastography of the placenta differs between normal pregnancies and pregnancies complicated by preeclampsia between 20 and 23 weeks' gestation. Methods: A prospective study was performed with 204 consecutive singleton pregnancies that had routine anomaly scanning between 20 and 23 weeks' gestation. One hundred twenty‐nine of these patients were examined with shear wave elastography; 101 women who had clinically normal pregnancies with normal fetal biometric measurements and normal deliveries without any perinatal complications formed group A, and 28 women who had a clinical diagnosis of early‐onset preeclampsia before anomaly scanning formed group B. Women with either posterior placentations (n = 63) or other obstetric disorders (n = 12) were excluded from the study. Results: Shear wave elastographic values for group B were significantly higher than those for group A ( P < .05). No statistically significant difference was found between the elasticity values measured at the center or edge of the placenta ( P > .05). Conclusions: Shear wave elastography differentiates between the placental elasticity of normal pregnancies and pregnancies complicated by preeclampsia when performed during the second trimester. As a new method for tissue characterization, shear wave elastography is useful for evaluation of placental function and can be used as a supplement to existing methods for prediction of preeclampsia.